Molecular Control of the Donor/Acceptor Interface Suppresses Charge Recombination Enabling High-Efficiency Single-Component Organic Solar Cells - Li, Yao (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 The Author(s). Advanced Materials published by Wiley‐VCH GmbH.